Acceptability of human papillomavirus self testing in female adolescents. Issue 5 (30th September 2005) - Kahn, J A; Bernstein, D I; Rosenthal, S L; Huang, B; Kollar, L M; Colyer, J L; Tissot, A M; Hillard, P A; Witte, D; Groen, P; Slap, G B
Abstract : Objectives: To develop scales assessing acceptability of human papillomavirus (HPV) testing in adolescents, to compare acceptability of self to clinician testing, and to identify adolescent characteristics associated with acceptability. Methods: Female adolescents 14–21 years of age attending a hospital based teen health centre self collected vaginal samples and a clinician, using a speculum, collected cervicovaginal samples for HPV DNA. Acceptability of and preferences for self and clinician testing were assessed at baseline and 2 week visits. Results: The mean age of the 121 participants was 17.8 years and 82% were black. The acceptability scales demonstrated good internal consistency, reliability, test-retest reliability, and factorial validity. Scores were significantly lower for self testing than clinician testing on the acceptability scale and three subscales measuring trust of the test result, confidence in one's ability to collect a specimen, and perceived effects of testing (p<0.01). Of those who reported a preference, 73% preferred clinician to self testing. Acceptability scores for both self and clinician testing increased significantly pre-examination to post-examination (p<0.01). Multivariable analyses demonstrated that race was independently associated with pre-examination and post-examination acceptability of self testing, and that sexual behaviours and gynaecological experiences were associated with specific acceptability subscales. Conclusions: This sample of adolescents found clinician testing for HPV to be more acceptable than self testing and preferred clinician to self testing. If self testing for HPV is offered in the future, clinicians should not assume that adolescent patients will prefer self testing. Instead, they should educate adolescents about available testing options and discuss any concerns regarding self collection technique or accuracy of test results.